HUBUNGAN ANEMIA PADA IBU HAMIL DENGAN PERDARAHAN POSTPARTUM AKIBAT ATONIA UTERI DI RSUD DR. PIRNGADI MEDAN - Harefa, Reinaldo F; Lumbanraja , Alex M; Yosa Mega, Juli (Jurnal Kedokteran Methodist, 2022)
Background: One of the risk factors for bleeding is anemia. Anemia in pregnancy is a condition of the mother with a hemoglobin count of 11 gg/dL in the first and third trimesters or a hemoglobin count of 10.5 g/dL in the second trimester. One of the causes of postpartum hemorrhage is uterine atony. Uterine atony is one of the 5th leading causes of maternal death globally. Uterine atony can cause bleeding after the baby is born due to the failure of the uterine myometrial muscle fibers to contract and shorten. Methods: The type of research used is quantitative research with a cross-sectional design. The study population was all pregnant women who gave birth at Dr. Hospital. The total sampling technique was used to select 50 pregnant women at term (37-42 weeks of gestation) for this study. Analysis of univariate and bivariate data using the chi-square test. Results: Based on the results of the study, it was found that the proportion of anemia in pregnant women with postpartum hemorrhage due to uterine atony in Dr. Pirngadi Medan's 2017–2021 was 52.9% (18 respondents). The results of statistical tests obtained a p value of 0.004, which means that anemia in pregnant women has a significant relationship with postpartum hemorrhage due to uterine atony. Conclusion: Based on the results of the study, it can be concluded that the anemia variable in pregnant women is a variable associated with postpartum hemorrhage due to uterine atony in Dr. Pirngadi Medan in 2017–2021.